2018
DOI: 10.1124/jpet.118.252890
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Chemokine Receptor Antagonists with Morphine Potentiates Morphine’s Analgesic Effect on Incisional Pain in Rats

Abstract: Crossdesensitization between opioid and chemokine receptors and involvement of chemokines in pain modulation are well established. We investigated if coadministration of chemokine receptor antagonists (CRAs) with morphine would enhance the analgesic potency of morphine on incisional pain in rats. Animals underwent incisional surgery on the left hind paw and pain responses were evaluated using von Frey filaments at various time points postsurgery between 15 and 360 minutes and daily between 24 and 72 hours. Dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Because of the significant changes in the levels of CCL7 and CCL11, the ligands of CCR3, the aforementioned receptor seems to be an interesting target for neuropathy treatment. Notably, blockade of other chemokine receptors in the CC family by their antagonists, e.g., CCR1 - J113863 ( 27 ), CCR2 - RS504393 ( 29 ), CCR4 - C021 ( 50 ), and CCR5 - maraviroc ( 31 , 61 ), beneficially modulates the changes observed during neuropathy, consistent with our previous reports ( 27 , 29 , 50 ). Therefore, we decided to use the CCR3 antagonist SB328437 to determine whether the blockade of this receptor would also be a beneficial pain treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Because of the significant changes in the levels of CCL7 and CCL11, the ligands of CCR3, the aforementioned receptor seems to be an interesting target for neuropathy treatment. Notably, blockade of other chemokine receptors in the CC family by their antagonists, e.g., CCR1 - J113863 ( 27 ), CCR2 - RS504393 ( 29 ), CCR4 - C021 ( 50 ), and CCR5 - maraviroc ( 31 , 61 ), beneficially modulates the changes observed during neuropathy, consistent with our previous reports ( 27 , 29 , 50 ). Therefore, we decided to use the CCR3 antagonist SB328437 to determine whether the blockade of this receptor would also be a beneficial pain treatment.…”
Section: Discussionsupporting
confidence: 91%
“…These results are summarized in Table . Similarly, previous report from our laboratory (Inan et al, ) showed that combining sub‐analgesic doses of morphine with chemokine receptor antagonists could provide maximal analgesia in a rat model of incisional pain.…”
Section: Discussionsupporting
confidence: 74%
“…Taken together, these studies suggest an extensive degree of regulation of the function of opioid receptors that is mediated by chemokine receptors. A very recent report shows that the co-administration of chemokine receptor antagonists potentiates the capacity of morphine to generate an analgesic response in a model of inflammatory pain (132). These results suggest that the results on heterologous desensitization can be clinically translated by interfering with the chemokine-mediated desensitization of MOP function in conditions involving inflammatory pain.…”
Section: Chemokine-induced Desensitization Of Opioid Receptorsmentioning
confidence: 88%
“…Pain is one of the cardinal signs of inflammation, and the mechanisms that are responsible for the increase in sensitivity to pain are complex. Elevated levels of pro-inflammatory chemokines have been measured at sites of chronic inflammation, and these chemokines contribute to the increase in pain sensitivity (132). Based on the knowledge of cross-talk between chemokine and opioid receptors, studies have been conducted to determine the capacity of various pro-inflammatory chemokines to induce heterologous desensitization of opioid receptors.…”
Section: Chemokine-induced Desensitization Of Opioid Receptorsmentioning
confidence: 99%